Shop Steward Performance: A Constrained-Decision Analysis - Fisher, E.G.; Reshef, Yonatan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
In managing their activities as workers and as shop stewards, stewards face various constraints. Using the results of a questionnaire, we identify which constraints seem to exert a greater influence on steward role performance. For instance, the issue being grieved seems to affect grievance resolution rates at step one. Key constraints investigated in regression analysis include: the nature of the parties' relationship, roleloads for stewards, training, and gender.